2021
DOI: 10.1101/2021.04.20.440637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachia cifBinduces cytoplasmic incompatibility in the malaria mosquito

Abstract: Wolbachia infections are a fascinating example of reproductive parasitism with strong potential to combat vector-borne diseases, due to their combined ability to spread in insect populations and block pathogen replication. Though the Wolbachia factors mediating the notable reproductive manipulation cytoplasmic incompatibility (CI) have now been identified as prophage WO genes cifA and cifB, the relative role of these genes is still intensely debated, with different models claiming that CI requires either both … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…At the genetic level, dual expression of cifA and cifB or single expression of cifB can recapitulate CI; and cifA rescues CI [13,[15][16][17][18][19]52]. However, the cellular and mechanistic bases of CI and rescue remain unresolved and the subject of several questions: When and where do the Cif proteins localize in testes to potentiate CI?…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic level, dual expression of cifA and cifB or single expression of cifB can recapitulate CI; and cifA rescues CI [13,[15][16][17][18][19]52]. However, the cellular and mechanistic bases of CI and rescue remain unresolved and the subject of several questions: When and where do the Cif proteins localize in testes to potentiate CI?…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that dual, transgenic expression of cifA and cifB from w Mel Wolbachia in Drosophila melanogaster males induces CI, while single expression of cifA in females rescues CI [ 16 , 17 ]. These results form the basis of the Two-by-One genetic model of CI for several, but not all, strains of Wolbachia [ 13 , 15 , 18 , 19 ]. At the cellular level, CI-defining lethality associates with chromatin defects and mitotic arrest within the first few hours of embryonic development.…”
Section: Introductionmentioning
confidence: 90%
“…Notably, the QxxxY motif is also present in T4 CifB of w Pip characterized as a DNase, present in T3 CifB of w No (Adams et al, 2021; Sun et al, 2021) and missing in T1 CifB of w Pip previously deemed to lack nuclease function (Chen et al, 2019). Thus, it is tentatively possible that the QxxxY motif may assist CifB DNase activity since it is localized in CTND, and the sites in CTND are proposed to be involved in substrate binding or catalytic regulation (Xiao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CI is governed by the Two-by-One genetic model demonstrated in various systems (Beckmann et al, 2019; Chen et al, 2019; LePage et al, 2017; Shropshire et al, 2021b; Shropshire and Bordenstein, 2019). cifB alone can also cause cifA -rescuable CI under a One-by-One genetic model (Adams et al, 2021; Sun et al, 2021). Therefore, deciphering the Cif molecular mechanism(s) and potentially universal features of CI and rescue remains a central goal for understanding how sexual reproduction serves as a battleground for host- Wolbachia interactions.…”
Section: Introductionmentioning
confidence: 99%